Parallel development and course of pheochromocytoma and giant squamous cell carcinoma of the leg: a new paraneoplastic syndrome? - Morais, Paulo (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
Paraneoplastic syndromes (PS) are diseases or symptom complexes associated with malignancy, usually of internal origin, but not directly related to mass effects, invasion, or metastatic spread. Rarely, cutaneous squamous cell carcinoma (SCC) may be associated with PS. We present a patient with a giant SCC located on the right leg and a pheochromocytoma. Considering the concurrent onset and parallel course of both pheochromocytoma and SCC in this patient, and the complete resolution of the endocrine abnormalities after resection of the skin tumor, it was possible to conceive of the pheochromocytoma as a paraneoplastic phenomenon. To our knowledge, this association has not been previously described.
Keywords: Adult; Carcinoma, Squamous Cell; dermatologija; Feokromocitom; karcinom; Karcinom ploščatocelični; Kožne novotvorbe; Odrasli; Paraneoplastic Syndromes; Paraneoplastični sindromi; Pheochromocytoma; rak (medicina); Skin Neoplasms